2014
DOI: 10.1007/s13277-014-2404-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) gene polymorphisms and breast cancer risk in Punjabi population from North West India

Abstract: The purpose of this study was to evaluate the association of seven VEGF promoter polymorphisms with breast cancer risk in Punjabi population from North West India. We screened DNA samples of 102 sporadic breast cancer patients and 102 unrelated healthy, gender, and age-matched individuals for seven VEGF promoter polymorphisms [-417 C/T (rs833062), -172 C/A (rs59260042), -165 C/T (rs79469752), -160 C/T, -152 G/A (rs13207351), -141 A/C (rs28357093) and -116 G/A (rs1570360)] by direct sequencing. The frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
2
13
1
Order By: Relevance
“…Previous studies have reported that high expression levels of VEGF are found in several kinds of solid tumors, and correlate with the promotion of microvessel density in tumor tissues (Ferrara, 2002). Epidemiologic studies have investigated the role of VEGF gene polymorphisms in the susceptibility to solid tumors such as breast, lung, colorectal, gastric, and prostate cancers (Zhou et al, 2011;Maeda et al, 2013;Chen et al, 2014;Kapahi et al, 2014;Jannuzzi et al, 2015). Kapahi et al (2014) conducted a study to evaluate the association of seven VEGF gene polymorphisms with the risk of breast cancer, and they found that the VEGF -152G/A and -116G/A polymorphisms significantly increased the risk of breast cancer, and that the VEGF -165C/T and -141A/C gene polymorphisms were correlated with a decreased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that high expression levels of VEGF are found in several kinds of solid tumors, and correlate with the promotion of microvessel density in tumor tissues (Ferrara, 2002). Epidemiologic studies have investigated the role of VEGF gene polymorphisms in the susceptibility to solid tumors such as breast, lung, colorectal, gastric, and prostate cancers (Zhou et al, 2011;Maeda et al, 2013;Chen et al, 2014;Kapahi et al, 2014;Jannuzzi et al, 2015). Kapahi et al (2014) conducted a study to evaluate the association of seven VEGF gene polymorphisms with the risk of breast cancer, and they found that the VEGF -152G/A and -116G/A polymorphisms significantly increased the risk of breast cancer, and that the VEGF -165C/T and -141A/C gene polymorphisms were correlated with a decreased risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have investigated the role of VEGF gene polymorphisms in the susceptibility to solid tumors such as breast, lung, colorectal, gastric, and prostate cancers (Zhou et al, 2011;Maeda et al, 2013;Chen et al, 2014;Kapahi et al, 2014;Jannuzzi et al, 2015). Kapahi et al (2014) conducted a study to evaluate the association of seven VEGF gene polymorphisms with the risk of breast cancer, and they found that the VEGF -152G/A and -116G/A polymorphisms significantly increased the risk of breast cancer, and that the VEGF -165C/T and -141A/C gene polymorphisms were correlated with a decreased risk of cancer. Maeda et al (2013) conducted a study in a Chinese population, and reported that the VEGF -460T/C polymorphism could influence tumor angiogenesis in nonsmall cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the SNPs À165 C/A (rs79469752), À152 A/G (rs13207351) and À141 A/C (rs28357093) only few epidemiological data are available. For À165 CT, À152 AA and À141 AC genotypes a differing risk was observed for North West Indian breast cancer patients [71].…”
Section: Breast Cancermentioning
confidence: 92%
“…22,21,12 VEGFA SNPs were shown to affect VEGFA levels in different cell models, 21,[23][24][25] including breast cancer. 26 VEGFA SNPs have also been associated with breast cancer susceptibility, 11,13,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] increased risk of progression 13,[40][41][42][43][44] or poor survival. 13,43 However, most of these works focused on the effects of SNPs evaluated separately, and the results from different authors present great disparity.…”
Section: Introductionmentioning
confidence: 99%